2022
DOI: 10.1021/acs.inorgchem.2c00727
|View full text |Cite
|
Sign up to set email alerts
|

Co–Fe–P Nanosheet Arrays as a Highly Synergistic and Efficient Electrocatalyst for Oxygen Evolution Reaction

Abstract: Supporting information for this article can be found under: https://doi.org/xx.xxxx/chem.xxxxxxxxx.Supporting information for this article can be found under: https://doi.org/xx.xxxx/chem.xxxxxxxxx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…The CPE element represents the surface porosity. An ideal electrocatalyst generally requires high surface area, porous structure, abundant active sites, and a synergic effect between the constituting components. Any of these characteristics can have a significant influence on the electrocatalytic performance. A high surface area and an increased content of the electroactive metal centers in the structure can increment the number of accessible active sites on the electrocatalyst surface.…”
Section: Resultsmentioning
confidence: 99%
“…The CPE element represents the surface porosity. An ideal electrocatalyst generally requires high surface area, porous structure, abundant active sites, and a synergic effect between the constituting components. Any of these characteristics can have a significant influence on the electrocatalytic performance. A high surface area and an increased content of the electroactive metal centers in the structure can increment the number of accessible active sites on the electrocatalyst surface.…”
Section: Resultsmentioning
confidence: 99%
“…Electrochemically splitting water into molecular hydrogen is fascinating because of its sustainable and carbon-neutral features. An alkaline water electrolyzer is closer to commercialization owing to the robustness of electrode and cheap electrolyzer construction. Yet, the hydrogen evolution reaction (HER) in alkaline electrolyte requires a larger overpotential to overcome its sluggish kinetics . Despite platinum (Pt)-based materials being regarded as the benchmark catalysts for HER, their performance in nonacidic media is still inferior.…”
mentioning
confidence: 99%
“…The enhanced activity was attributed to the following aspects: (1) Fe 3+ modulation increased the surface oxophilicity of Ru and endowed it with a stronger capability for water molecule adsorption and dissociation, leading to an accelerated Volmer step. (2) The high electronegativity of incorporated Fe 3+ attracted more electrons from Ru and thus weakened the hydrogen combination and facilitated H 2 desorption, providing a rapid Heyrovsky process. (3) Rich defects and lattice distortions were induced during Al 3+ leaching and Fe 3+ incorporation, which were conducive to exposing more active sites for hydrogen production.…”
mentioning
confidence: 99%
“…To date, extensive efforts have been devoted to the earth-abundant transition metal-based compounds, which are regarded as highly promising candidates to replace precious metal-based catalysts. , In particular, cobalt (Co)-based layered double hydroxides (LDHs) or oxides with favorable catalytic activity are the focus of attention according to their richly variable valence states, good corrosion stability in alkaline medium, and environmental friendliness. It is worth mentioning that, since an increase in the 3D energy band centers from late to early transition metals in the periodic table, Co-based catalysts exhibit higher binding energies for oxygen intermediates at the Co active site compared to the nickel (Ni)-based LDHs. , Unfortunately, the insufficiently exposed active sites of LDHs or the intrinsically low conductivity of oxides greatly restrict further improvements in the OER catalytic performance. , Quite a few recent studies have shown that the design strategies for specific nanostructures, such as self-supported nanosheets, nanotubes, nanowire arrays, and so forth, can usefully enhance the electrical conductivity and supply a high specific surface area with increased catalytic sites while successfully coping with the negative effects of binders. , More importantly, interfacial engineering, for example, three-dimensional (3D) core/shell heterostructure, can endow the composite catalysts with an outstanding electrocatalytic activity over their single-component counterparts, mainly due to the strong interfacial electronic coupling between different components. A number of advanced non-precious metal catalysts possessing heterostructures continue to be reported. Yu et al developed a composite electrocatalyst with highly efficient catalytic activity and excellent stability in alkaline media by tailoring cobalt tetroxide (Co 3 O 4 )/Co nano-heterojunctions in nitrogen-doped porous graphitized carbon frameworks . In addition, this approach can effectively avoid the aggregation and stacking of ultrathin LDHs to expose more active sites and accelerate mass diffusion. , Over the past few years, a series of catalysts integrating NiFe-LDH and transition metal oxides on metal substrates (e.g., nickel foam) to construct heterojunctions have displayed excellent OER catalytic performance for water splitting. , In the meantime, the relevant reports on energy storage devices mainly concentrate on liquid ZABs. , Given the unique advantages of Co-based catalysts, the heterostructured catalysts based on Co-based LDHs are expected to achieve high OER catalytic capacity, which has been of considerable interest in the field of water splitting lately. , Nevertheless, the application of such hybrid catalysts in ZABs and flexible energy storage devices still demands further exploration and...…”
Section: Introductionmentioning
confidence: 99%